Arctic stratospheric dehydration - Part 1: Unprecedented observation of vertical redistribution of water - Khaykin, Sergey; Engel, I.; Vömel, H.; Formanyuk, I. M.; Kivi, R.; Korshunov, L. I.; Krämer, M.; Lykov, A. D.; Meier, S.; Naebert, T.; Pitts, M. C.; Santee, M. L.; et al. (Atmospheric Chemistry and Physics, 2013)
We present high-resolution measurements of water vapour, aerosols and clouds in the Arctic stratosphere in January and February 2010 carried out by in-situ instrumentation on balloon-sondes and high-altitude aircraft combined with satellite observations. The measurements provide unparalleled evidence of dehydration and rehydration due to gravitational settling of ice particles. An extreme cooling of the Arctic stratospheric vortex during the second half of January 2010 resulted in a rare synoptic-scale outbreak of ice PSCs (polar stratospheric clouds) detected remotely by the lidar aboard the CALIPSO satellite. The widespread occurrence of ice clouds was followed by sedimentation and consequent sublimation of ice particles, leading to vertical redistribution of water inside the vortex. A sequence of balloon and aircraft soundings with chilled mirror and Lyman-α hygrometers (CFH, FISH, FLASH) and backscatter sondes (COBALD) conducted in January 2010 within the LAPBIAT and RECONCILE campaigns captured various phases of this phenomenon: ice formation, irreversible dehydration and rehydration. Consistent observations of water vapour by these independent measurement techniques show clear signatures of irreversible dehydration of the vortex air by up to 1.6 ppmv in the 20-24 km altitude range and rehydration by up to 0.9 ppmv in a 1 km-thick layer below. Comparison with space-borne Aura MLS water vapour observations allow the spatiotemporal evolution of dehydrated air masses within the Arctic vortex to be derived and upscaled.